SUPERVISION OF THE IMPLEMENTATION OF NOMINATION FUNCTIONS RELATED TO CHANGES OF MANAGEMENT IN A PUBLIC COMPANY - Yunita Endah Lestari; Daly Erni (Awang Long Law Review, 2022)
This study discusses the conditions of supervision carried out by the Financial Services Authority (OJK) in supervising the implementation of the provisions contained in Article 7 and Article 26 of the Financial Services Authority Regulation Number 33/POJK.04/2014 concerning the Board of Directors and Board of Commissioners of Issuers or Public Companies and Article 8 point a Financial Services Authority Regulation No. 34/POJK.04/2014 concerning the Nomination and Remuneration Committee of Issuers or Public Companies regarding the obligation to obtain recommendations from the board of commissioners or the nomination committee for the appointment, replacement and/or dismissal of members of the board of directors and board of commissioners of a public company. The Board of Directors and the Board of Commissioners are organs of a limited liability company whose appointment, replacement and/or dismissal must be carried out in accordance with the provisions of laws and regulations. However, in reality there is a violation committed by the public company of the above obligations as can be seen based on the Central Jakarta District Court Decision Number 660/Pdt.G/2019/PN Jkt.Pst. The study was conducted using a normative juridical research method by examining secondary data in the form of documents and regulations. Furthermore, to strengthen and confirm the data, interviews were also conducted with authorized officials at OJK.